WHY WORD-OF-MOUTH IS IMPORTANT FOR MEDICAL TOURISM? A QUALITATIVE STUDY - Ching Ying Tian; Seow Ai Na; Lam Siew Yong (International Journal of Accounting, Finance and Business, 2023)
Medical tourists make decisions for medical services abroad partly based on their perceptions through word-of-mouth. The information about a travel destination affects both the actual travel experience and post-travel behaviour. As a result, word-of-mouth marketing (WOM) is frequently cited as one of the most effective ways of advertising in this industry. Still, there is a need to have more research that explores the reasons behind these medical tourists' referrals. This qualitative study seeks to fill this research gap by examining what triggers medical tourists' word-of-mouth generation. Semi-structured interviews were conducted with five respondents with medical treatment experience from one of the medical tourism-certified hospitals in Malaysia. The thematic analysis method was used to analyse the data. Fifteen reasons were identified that triggered their word-of-mouth and were divided into four elements: treatment quality, quality of interaction, quality of processes, and the overall service and facilities of the hospital. It was found that medical tourists who are satisfied with the medical services value of the hospital abroad will spread word-of-mouth and recommend it to others. This research offers practical standpoints on the creation of word-of-mouth in the context of medical tourism. It suggests ways for industry stakeholders to gain from this effective promotional strategy.